2012
DOI: 10.1007/s10456-012-9302-0
|View full text |Cite
|
Sign up to set email alerts
|

Highly potent VEGF-A-antagonistic DARPins as anti-angiogenic agents for topical and intravitreal applications

Abstract: The next-generation ophthalmic anti-VEGF therapeutics must aim at being superior to the currently available agents with regard to potency and improved drug delivery, while still being stable and safe to use at elevated concentrations. We show here the generation of a set of highly potent VEGF-A antagonistic DARPins (designed ankyrin repeat proteins) delivering these properties. DARPins with single-digit picomolar affinity to human VEGF-A were generated using ribosome display selections. Specific and potent hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…A VEGF-A antagonistic DARPin that selectively binds VEGF-A with an apparent IC 50 of 10 pM has been shown to suppress suture-induced corneal NV in rabbits and laser-induced choroidal NV in rats after topical administration [14]. In the current study, we have extended those findings to show that systemic administration of an anti-VEGF-A DARPin reduces laser-induced choroidal NV in mice and reduces the incidence and severity of exudative retinal detachments in a particularly severe model, Tet/opsin/VEGF double transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A VEGF-A antagonistic DARPin that selectively binds VEGF-A with an apparent IC 50 of 10 pM has been shown to suppress suture-induced corneal NV in rabbits and laser-induced choroidal NV in rats after topical administration [14]. In the current study, we have extended those findings to show that systemic administration of an anti-VEGF-A DARPin reduces laser-induced choroidal NV in mice and reduces the incidence and severity of exudative retinal detachments in a particularly severe model, Tet/opsin/VEGF double transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Libraries have been constructed to produce DARPins with random surface that can be screened for binding to target proteins [12, 13]. A DARPin that selectively binds VEGF-A with a Kd of 2 pM has been characterized and when injected into the vitreous cavity of rabbits, it suppresses VEGF-induced leakage [14]. It also suppresses laser-induced choroidal NV in rats after topical administration to the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies indicate that dosing frequency in patients may be reduced compared with current therapy (67). A phase I dose escalation study demonstrated the overall safety and efficacy of MP0112 (NCT01086761) (68).…”
Section: Figurementioning
confidence: 99%
“…From such combinatorial libraries DARPins with high affi nities have been selected, normally via ribosome display, against a variety of proteins, including several medically relevant targets: for example, HIV gp120 (Mann et al 2013 ;Schweizer et al 2008 ), EpCAM (Stefan et al 2011 ), Alzheimer amyloid-β peptide (Aβ) (Hanenberg et al 2014 ) and, as will be described in greater detail below, VEGF-A (Stahl et al 2013 ). Since the advantageous biophysical properties of the parental ankyrin scaffold such as high-level expression, solubility, and stability are often retained in these DARPins, they are also well suited for the generation of multispecifi c constructs (Molecular Partners, http://www.molecularpartners.com ).…”
Section: Darpinsmentioning
confidence: 99%